E-commerce development and household consumption growth in China - Luo, Xubei; Wang, Yue; Zhang, Xiaobo (2019)
China has quickly become the largest e-commerce market in the world. E-commerce has reshaped consumption patterns in recent years. This paper examines how e-commerce development has shaped household consumption growth in China. It finds that e-commerce development is associated with higher consumption growth, that the link is stronger for the rural sample, inland regions, and poor households, and that the consumption of durable goods, in-style goods, and goods of high income elasticity have grown faster than the consumption of local services.